The N-glycome of the hemipteran pest insect Nilaparvata lugens reveals unexpected sex differences. (April 2019) - Scheys, Freja; De Schutter, Kristof; Shen, Ying; Yu, Na; Smargiasso, Nicolas; De Pauw, Edwin; Van Damme, Els J.M.; Smagghe, Guy
Abstract: The brown planthopper, Nilaparvata lugens, is a model species for hemimetabolous development and the most important pest insect in rice, which is the major staple crop for about half of the world population. Despite its importance, little is known of the N -glycosylation process in this insect. Here we report on the N -glycome for the post-embryonic stages of N. lugens, revealing unique features that are different from the holometabolous insect models, as the fruit fly Drosophila melanogaster and the beetle Tribolium castaneum . Analysis of the N -glycan fingerprint for male and female adults showed sex-specific N -glycosylation in insects. Specifically, the female adults progress towards a unique glycan profile with a striking increase in high mannose N -glycans. The N -glycome of N. lugens contributes to study pathways differentiating between sexes, and the results shed light on the evolution and differences in development between primitive hemimetabolous insects and more advanced holometabolous insects. The data are discussed in relation to potential function(s) in development and sex specificity. Graphical abstract: Image 1 Highlights: N -glycome of a hemimetabolous model and important pest insect, the rice planthopper Nilaparvata lugens, has been resolved. High mannose and monofucosylated N -glycans dominate the N -glycome of N. lugens . Analysis of the N -glycan fingerprint showed sex-specific N -glycosylation.